2021
DOI: 10.3389/fcell.2021.752753
|View full text |Cite
|
Sign up to set email alerts
|

Periphery Biomarkers for Objective Diagnosis of Cognitive Decline in Type 2 Diabetes Patients

Abstract: Introduction: Type 2 diabetes mellitus (T2DM) is an independent risk factor of Alzheimer’s disease (AD), and populations with mild cognitive impairment (MCI) have high incidence to suffer from AD. Therefore, discerning who may be more vulnerable to MCI, among the increasing T2DM populations, is important for early intervention and eventually decreasing the prevalence rate of AD. This study was to explore whether the change of plasma β-amyloid (Aβ) could be a biomarker to distinguish MCI (T2DM-MCI) from non-MCI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…41 We have also reported that the platelet GSK-3β activity could be a peripheral biomarker for MCI, because it showed increase in T2DM with MCI (T2DM-MCI) patients compared to T2DM without MCI (T2DM-nMCI). 12,[42][43][44] However, how peripheral insulin homeostasis influence CNS is an important future direction. 45,46 GSK-3β inhibitors hold therapeutic potentials for T2DM and AD possibly by preventing the aggregation of β-amyloid (Aβ), inhibiting the hyperphosphorylation of tau protein, or reducing neuroinflammation in animal models, [47][48][49][50] but their effectiveness for improving cognitive impairment need further proof.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…41 We have also reported that the platelet GSK-3β activity could be a peripheral biomarker for MCI, because it showed increase in T2DM with MCI (T2DM-MCI) patients compared to T2DM without MCI (T2DM-nMCI). 12,[42][43][44] However, how peripheral insulin homeostasis influence CNS is an important future direction. 45,46 GSK-3β inhibitors hold therapeutic potentials for T2DM and AD possibly by preventing the aggregation of β-amyloid (Aβ), inhibiting the hyperphosphorylation of tau protein, or reducing neuroinflammation in animal models, [47][48][49][50] but their effectiveness for improving cognitive impairment need further proof.…”
Section: Discussionmentioning
confidence: 99%
“…Platelets, the peripheral synaptic vesicles, also share many of the same secretory pathways and transporters as the synaptic terminals of neurons during neurotransmitter uptake and packaging 41 . We have also reported that the platelet GSK‐3β activity could be a peripheral biomarker for MCI, because it showed increase in T2DM with MCI (T2DM‐MCI) patients compared to T2DM without MCI (T2DM‐nMCI) 12,42–44 . However, how peripheral insulin homeostasis influence CNS is an important future direction 45,46 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation